PENGARUH PENGADOPSIAN IFRS DAN GOOD CORPORATE GOVERNANCE TERHADAP KUALITAS LABA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2013) - Ulian Febriansyah Dalimunthe; Agus Purwanto (Diponegoro Journal of Accounting, 2015)
This research aims to examine the effect of IFRS adoption and good corporate governance on earnings quality. Adoption of IFRS is measured by dummy variable. The proxy of good corporate governance   are   audit   committee,   independent   commisoner,   institutional   ownership,   and managerial ownership. The dependent variable in this research is quality earnings measured by discretionary accrual using modified Jones to detect earning management. The population in this research are all of manufacturing companies listed in Indonesia Stock Exchange in 2010-2013. The sampling method in this research uses purposive sampling method. The analytical method in this research  is  regression  analysis  after  tested  by  classical  assumption  tests.  The  results  of  this research  find  that  IFRS  adoption  has  significantly  positive  effect  on  earnings  quality.  IFRS adoption can increase earnings quality. Other independent variables i.e. audit committe, independent commisoner, institutional ownership, and managerial ownership have no significantly effect on earnings quality.